CANCER-RELATED FATIGUE IN THE CONTEXT OF AGING: WHAT ARE WE REALLY MEASURING AND WHY DOES IT MATTER?. (11th November 2018) - Walker, R K; Kent, J
Abstract: Cancer-related fatigue (CRF) significantly interferes with cancer survivors' ability to carry out necessary and valued activities of daily living. In March 2018, JAMA Oncology published a critique of a recent meta-analysis of CRF interventions. The critique asserted symptoms such as fatigue do not concretely exist, and therefore cannot be accurately measured. Meta-analysis authors countered by arguing that CRF does exist and can be validly measured. The purpose of this symposium is to extend this debate about the state of science of CRF measurement, in the context of aging. To introduce the debate, Dr. Walker will briefly review current conceptual and operational definitions of fatigue in cancer and aging research. Dr. Wood will illustrate several of these definitions with self-report and objective data from a study of physical function among chronically-fatigued adult cancer survivors. Dr. Bryant will then present age-related patterns in prospectively-collected PROMIS measures of CRF among newly-diagnosed adult leukemia patients undergoing induction chemotherapy. Dr. Walker will extend the discussion with data from an eyetracking study involving PROMIS and objective measures of fatigue and function among breast cancer survivors and age-matched controls. Relationships between hormonal factors and the phenotype of CRF, sexual dysfunction and lean body mass among older male cancer survivors will be presented by Dr. Berry. Dr. Kent will then facilitate a scholarly conversation about what we are doing when we assess and interpret measures of fatigue in the context of cancer and aging, and implications for best practices in research and clinical assessment.